2015
DOI: 10.1016/j.rboe.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic study on the tibial insertion of the posterior cruciate ligament

Abstract: ObjectiveTo establish the radiographic distances from posterior cruciate ligament (PCL) tibial insertions centers to the lateral and medial tibial cortex in the anteroposterior view, and from these centers to the PCL facet most proximal point on the lateral view, in order to guide anatomical tunnels drilling in PCL reconstruction and for tunnel positioning postoperative analysis.Study designControlled laboratory study.MethodsTwenty cadaver knees were evaluated. The PCL's bundles tibial insertions were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Much of the literature has focused on biomechanical and functional outcomes when comparing various PCLR techniques. 7,12,22,31,41,48 However, there is a growing body of information regarding patient function following isolated PCLR, including whether patients can expect RTS following surgery. The aim of this study was to systematically review and synthesize the literature to determine the functional outcome and rate of RTS and activity following isolated PCLR.…”
mentioning
confidence: 99%
“…Much of the literature has focused on biomechanical and functional outcomes when comparing various PCLR techniques. 7,12,22,31,41,48 However, there is a growing body of information regarding patient function following isolated PCLR, including whether patients can expect RTS following surgery. The aim of this study was to systematically review and synthesize the literature to determine the functional outcome and rate of RTS and activity following isolated PCLR.…”
mentioning
confidence: 99%
“…In order to obtain more reliable anatomical information regarding PCL, multiple researchers reported various methods. Gali and colleagues reported that the PCL bundle's tibial insertions can be identified and marked using metal tags, prior to knee radiography 23 . Van Hoof T reported that a contrast medium injected before computed tomography (CT) imaging of the knee can segment and render in 3D imaging, thus, facilitating morphological and morphometric analysis of the PCL 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, variability of the PCL laxity exists among normal subjects. In addition, cadaveric studies have revealed a wide variation of attachment site and course of fiber for the PCL ( 16 19 20 21 ). Depending on the variability of the physiologic laxity and anatomical course of the PCL, interposition of the PCL into the medial compartment of the knee joint may have been scanned on coronal MRI.…”
Section: Discussionmentioning
confidence: 99%